Peranan Komite Sekolah dalam Meningkatkan Mutu Pendidikan Dasar di Kota Madiun - Agus Budi Santoso; Sumani Sumani (Jurnal Pendidikan, 2011)
Learning is a teaching learning process through the creation of comfortable and effective learning environment. In general, contextual learning is considered as a concept which helps teachers relate the content of the learning material to the real situation and drive students to make some relationship between the working knowledge and its application in their lives as family as well as society members. This research is aimed at (1) describing that the result of IPS learning through CTL with the best benefit of environment as the learning source is better than conventional learning, (2) describing that students response toward CTL leaning with the best benefit of environment as the learning source is better than conventional learning, (3) describing the existing constraints when the learning through CTL is at work. The research design is of experimental feature with two group pretest-posttest design. The subjects of this research cover forty four-year students of State Elementary School 01 Kartoharjo Madiun each for experimental group or class and control group or class. The research instruments used to collect the data include questionnaire, learning test, and observation sheet. Based upon the result of the analysis it is found that (1) the learning result of the students joining the CTL learning activities is better when compared with that of those joining the conventional learning. The mean of the experimental class after the treatment of CTL learning is 83 while the mean of the control class with conventional learning is 62.68; (2) the students’ response towards the implementation of CTL learning is generally positive, (3) the existing constraints are due to the fact that the learning facilities and time allotment are limited and the number of the students is too big. The conclusion is that the research using CTL learning indicates better learning result and better students’ response than that of conventional learning.